DISKURSUS ISLAM DALAM KONSTRUKSI MEDIA - Fahmi, Muhammad; Abdullah, Irwan; Noviani, Ratna; Udasmoro, Wening (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2015)
This paper aims to examine how the secular media in Surakarta represent Islam in the case of Charlie Hebdo. Therefore, this study used discourse analysis of Theo van Leeuwen focusing on how the subject or actor of the show in the media. This study concluded that the media represent Islam not only with “Western ideology” through idioms such as radical Islamist militants and terrorists, but also with "Islamic ideology". It is done through the construction of Islam as a religion of moderation and delegitimize Charlie Hebdo as magazine satyr abusing freedom. Various strategies are used ranging from strategy passivation to interdetermination. In this case, there are two poles of attraction in both media, namely the Western and Islamic ideology. If both media are quoting from Western sources, the Western ideology dominates the media narrative. Conversely, when both media used Islamic sources, the influence of Islamic ideology dominates the narrative of both media.